Retinal and choroidal changes observed with 'En face' enhanced-depth imaging OCT in central serous chorioretinopathy. Issue 9 (3rd July 2013) - Lehmann, Mathieu; Wolff, Benjamin; Vasseur, Vivien; Martinet, Virginie; Manasseh, Nadine; Sahel, José Alain; Mauget-Faÿsse, Martine
Abstract : Aims: To describe retinal and choroidal changes in acute and quiescent central serous chorioretinopathy (CSC) observed with 'En face' spectral domain optical coherence tomography (SD OCT) combined with enhanced-depth imaging (EDI). Methods: A prospective and descriptive study at the Rothschild Ophthalmologic Foundation (Paris, France) between September 2011 and February 2012. Eyes with a clinical diagnosis of CSC were examined using SD OCT with EDI, fluorescein and indocyanine green angiography. 3D reconstruction of 197 transverse sections with SD OCT, spaced of 30 μ, provided a virtual macular brick through which 496 sections in the coronal plane resulted in a C-scan or En face OCT image. Results: 23 of 29 eyes (79%) had serous retinal detachment (all active CSC) and 22 had pigment epithelial detachment (75%). Pigment epithelial hyperplasia was visualised in nine eyes (31%). Posterior cystoid retinal degenerations were present in five eyes (17%). The mean choroidal thickness was 491.5 μ. In 11 eyes (38%), En face OCT showed multiple hyper reflective points located at the level of the choriocapillary layer and choroidal cavitations were found in two patients. Conclusions: En face OCT imaging using SD OCT is an easy, reproducible, non-invasive and effective tool to understand choroidal changes in acute and quiescent CSCR. It provides complementary morphological information, describes new semiological entities and might substitute other exams in the future.